High comprehensive electrocaloric performance in barium titanate-based ceramics via integrating diffuse phase transition near room temperature and a high applied electric field. Issue 5 (1st March 2022) - Zhang, Amei; Hou, Hongping; Liao, Na; Miao, Zhuang; Wang, Xin; Liu, Jia; Du, Hongliang; Wei, Fangbin; Zhang, Leiyang; Jin, Li
Abstract: Lead-free relaxor bulk ceramics (LFRBCs) have the advantages of environment-friendliness, diffuse phase transition near room temperature (RT) and large heat absorption capacity, so as to be candidates for medium and large electric refrigeration and cooling equipment. Although considerable efforts have been made to explore LFRBCs with a large adiabatic temperature change (Δ T ) near room temperature, the RT Δ T of LFRBCs is still too weak, baffling their practical applications. In addition, common strategy for achieving a large RT Δ T is mainly tuning phase transitions by compositional engineering. Unfortunately, this strategy is not enough to realize the required properties for EC cooling devices. In this work, based on the general phenomenological expressions of EC effect, we proposed a new strategy, i.e. coordinated regulation of phase transitions and applied electric fields, to achieve a large RT Δ T and a wide using temperature range in LFRBCs simultaneously. Encouragingly, the Δ T calculated using the indirect method inclines from 0.96 K to 1.7 K ranging from 300 K to 360 K in 0.25 mol. % La 3+ doped Ba(Zr0.2 Ti0.8 )O3 ceramic under electric field change of 150 kV cm −1, which is much higher than that calculated using the indirect method so far in many LFRBCs designed using previous strategy for EC refrigeration, demonstrating a big step in LFRBCs for EC refrigeration. The large RT Δ T and broad operating temperature range are mainly attributed to diffuse phase transition near room temperature and a high applied electric field. Most importantly, this work provides a significant guideline to develop new LFRBCs with high comprehensive EC properties for high-efficiency cooling devices, which will bring a series of new LFRBCs with a large room-temperature Δ T in a wide temperature range for next-generation refrigeration in the future.